Mitochondrial DNA Depletion Syndrome and Its Associated Cardiac Disease - Wang, Haiying; Han, Yijun; Li, Shenwei; Chen, Yunan; Chen, Yafen; Wang, Jing; Zhang, Yuqing; Zhang, Yawen; Wang, Jingsuo; Xia, Yong; Yuan, Jinxiang (Frontiers in Cardiovascular Medicine, 2022)
Mitochondria is a ubiquitous, energy-supplying (ATP-based) organelle found in nearly all eukaryotes. It acts as a “power plant” by producing ATP through oxidative phosphorylation, providing energy for the cell. The bioenergetic functions of mitochondria are regulated by nuclear genes (nDNA). Mitochondrial DNA (mtDNA) and respiratory enzymes lose normal structure and function when nuclear genes encoding the related mitochondrial factors are impaired, resulting in deficiency in energy production. Massive generation of reactive oxygen species and calcium overload are common causes of mitochondrial diseases. The mitochondrial depletion syndrome (MDS) is associated with the mutations of mitochondrial genes in the nucleus. It is a heterogeneous group of progressive disorders characterized by the low mtDNA copy number. TK2, FBXL4, TYPM, and AGK are genes known to be related to MDS. More recent studies identified new mutation loci associated with this disease. Herein, we first summarize the structure and function of mitochondria, and then discuss the characteristics of various types of MDS and its association with cardiac diseases.